Modelling Fallschirmjäger Figures 'Tactical withdrawl' Fallschirmjäger on the Eastern Front, 1944 : In 1/35 scale /: In 1/35 scale. (2012 copyright 2012) - Forns, Jaume Ortiz; Romero, Daniel Alfonsea
No abstract available